Administrative Principles, Processes And Practice: An Overview - ugo CHUKS okolie (Universitas Kuningan, 2021)
For all administrative activities to be purposeful and effective, they must be governed by some fundamental rules and regulations that help the administrator to determine what to do in a given problem situation. It is these fundamental rules and regulations that are normally referred to as “principles of administration”. For organization to achieve its set goals and objectives, administrators are required not only to deal with the traditional concerns of administration and management, policy development and service delivery but increasingly, the job of administrators in contemporary times will be that of fostering citizenship and identifying, creating and managing public values by applying administrative principles and processes. Therefore, an overview of administrative principles, processes and practice is the objective of this paper. This paper adopted qualitative research design and draws its argument basically from secondary data which include journal articles, textbooks and internet sources. Finally, the paper concludes that organization will grow from strength to strength if administrators will stick strictly to the general goals and objectives of the organization through the implementation of the 29 administrative principles